2022
DOI: 10.1111/jan.15230
|View full text |Cite
|
Sign up to set email alerts
|

Patients′ and clinicians′ experiences of remote consultation? A narrative synthesis

Abstract: Aims To identify, evaluate and summarize evidence of patient and clinician experiences of being involved in video or telephone consultations as a replacement for in‐person consultations. Design Narrative synthesis. Data sources Medline; EMBASE; EMCARE; CINAHL and BNI. Searching took place from January 2021 to April 2021. Papers included were published between 2013 and 2020. Review Methods Papers were appraised by two independent reviewers for methodological quality. Data extraction was conducted according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…'Provider perceptions, attitudes, and concerns' (in relation to communication systems) were also frequently found to in uence the impact of eHealth on patient-provider relationships and trust. Although negative provider perceptions about technology sometimes seemed to have a negative impact on the patient-provider relationship, 99,68 we found that these perceptions could change after providers use technology (see for example Walthall et al, 90 Bassi et al, 100 Brewster et al, 101 and Sharma et al 102 ). We also found that there were some discrepancies between providers' perceptions of patient expectations and patients' actual expectations regarding technology use (see for example Brewster et al 101 ).…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…'Provider perceptions, attitudes, and concerns' (in relation to communication systems) were also frequently found to in uence the impact of eHealth on patient-provider relationships and trust. Although negative provider perceptions about technology sometimes seemed to have a negative impact on the patient-provider relationship, 99,68 we found that these perceptions could change after providers use technology (see for example Walthall et al, 90 Bassi et al, 100 Brewster et al, 101 and Sharma et al 102 ). We also found that there were some discrepancies between providers' perceptions of patient expectations and patients' actual expectations regarding technology use (see for example Brewster et al 101 ).…”
Section: Discussionmentioning
confidence: 73%
“…54 One review noted that patients and providers felt that the ability of remote consultations to facilitate patient empowerment and participation could change as the patient's illness progressed. 90 3. Sociodemographic factors were related to relationships and trust in 10 reviews, mostly focusing on communication systems.…”
Section: Conceptualization Of Relationships and Trustmentioning
confidence: 99%
See 3 more Smart Citations